Significant Associations between Chlamydia trachomatis and Neisseria gonorrhoeae Infections in Human Immunodeficiency Virus-Infected Pregnant Women - Bongekile Ngobese; Khine Swe Swe-Han; Partson Tinarwo; Nathlee S. Abbai (Hindawi Limited, 2022)
There is a lack of data on the burden of Chlamydia trachomatis and Neisseria gonorrhoeae among human immunodeficiency virus- (HIV-) infected pregnant women in South Africa. We conducted a cross-sectional study which included 385 HIV-infected pregnant women attending antenatal clinic at the King Edward VIII Hospital in Durban, South Africa. The women provided vaginal swabs which were tested for C. trachomatis and N. gonorrhoeae. The prevalence of the individual STIs was as follows: C. trachomatis (47/385, 12.2%) and N. gonorrhoeae (16/385, 4.1%). Having a circumcised partner, testing positive for N. gonorrhoeae, and perceiving themselves of being at risk for infection were shown to increase the risk for C. trachomatis infection. Without controlling for the other factors, testing positive for N. gonorrhoeae increased the risk for C. trachomatis infection by 10-fold (OR: 10.17, 95% CI: 3.39-29.66, p<0.001). Similarly, adjusting for the other factors, the risk for C. trachomatis infection in women who tested positive for N. gonorrhoeae was 9-fold (OR: 9.16, 95% CI: 2.19-40.18, p=0.003). The following factors were associated with the increased risk of N. gonorrhoeae infection: not knowing their partner's HIV status, partner having other partners, and C. trachomatis infection status. Without controlling for the other factors, testing positive for C. trachomatis increased the risk for N. gonorrhoeae infection by 6-fold (OR: 6.52, 95% CI: 2.22-18.49, p<0.001). Similarly, adjusting for the other factors, the risk for N. gonorrhoeae infection in women who tested positive for C. trachomatis was 6-fold (OR: 6.09, 95% CI: 1.73-22.03, p=0.005). We found a significant association between C. trachomatis and N. gonorrhoeae in the pregnant women and the risk factors associated with these pathogens. Future studies are urgently required to investigate the impact of C. trachomatis/N. gonorrhoeae coinfections in HIV pregnant women since this data is lacking in our setting. In addition, etiological screening of C. trachomatis and N. gonorrhoeae during antenatal clinic is urgently required to prevent adverse pregnancy and birth outcomes associated with these infections.